The Medicalization of Sleeplessness: A Public Health Concern - Moloney, Mairead Eastin (American Public Health Association, 2011)
Sleeplessness, a universal condition with diverse causes, may be increasingly diagnosed and treated (or medicalized) as insomnia. We examined the trend in sleeplessness complaints, diagnoses, and prescriptions of sedative hypnotics in physician office visits from 1993 to 2007. Consistent with the medicalization hypothesis, sleeplessness complaints and insomnia diagnoses increased over time and were far outpaced by prescriptions for sedative hypnotics. Insomnia may be a public health concern, but potential overtreatment with marginally effective, expensive medications with nontrivial side effects raises definite population health concerns.